Understanding the relation between serious surfing, surfing profile, surf travel behaviour and destination attributes preferences - Portugal, Ana Cristina; Campos, Francisco; M. L. Martins, Fernando; Melo, Ricardo (Varna University of Management, 2017)
Surfing is a sportingactivity that has become a major business, integrated in the leisure and tourism industries. Due to the impact of surf tourism and to the surfers’ characteristics featured by the time and effort they invest in surfingand their propensity to travel in search for the perfect wave, it is importantto understand if the six serious leisure qualities(perseverance, career, effort, benefits, ethos andidentity) are related with socio-demographic characteristics, surfing profile, surf travel behaviour and surfing destination attributes preferences. Aimingtoachieve these goals, an online survey (in the form of a questionnaire) was applied to a casual sample of 200 surfers in Portugal. The results of this study demonstrate that surfers exhibit the six serious leisure qualities and have a strong disposition to travel for surfing. Moreover, the results highlight that surfers value mainly the surfing natural conditions when choosing a surfing travel destination. Statistical tests also allowed concluding that socio-demographic variables are not good predictors of serious surfing, although serious surfingis correlated with surfing profile, surf travel behaviour and surfing destination attributes preferences.This data enables to provide important information that can be used to strengthen management strategies by surf tourism industry providers.
Keywords: destination attributes preferences; serious leisure; sport tourism; surf tourism; travel behaviour